(untitled) (Global Journal of Science Frontier Research, 2018)
In this note the authors generalize the linear Cauchy-Euler ordinary differential equations ODEs into nonlinear ODEs and provide their analytic general solutions Some examples are presented in order to clarify the applications of interesting results